The Importance of the Participation of the Medical Expert in Criminal Proceedings - Szilvássy Zoltán (PÁZMÁNY LAW REVIEW, 2024)
The Criminal Procedure Act significantly changed the rules of expert evidence, so e.g. in order to prevent the prolongation of the procedures, it attempts to direct the process of appointing experts and evaluating expert opinions into a reasonable channel in order to make a considered and timely decision. The time that has passed since the entry into force of the law already allows us to examine the practice of law enforcement. I believe that the biggest change comes from the regulation of the private expert opinion, which allows the defendant and his defense to have equalrights in the criminal proceedings, which also follow from the principle of equality of arms. And all of this strengthens the fairness of the procedure in general, which can be a guarantee of the birth of judicial verdicts that are also close to the material truth.